First Report on HHV-6 Infection Among HIV-Infected Individuals Residing in Surabaya, Indonesia - Oktafiani D (Dove Medical Press, 2020)
Devi Oktafiani,1 Ni Luh Ayu Megasari,1,2 Elsa Fitri Ana,1 Nasronudin,1,3 Maria Inge Lusida,2,4 Soetjipto2,3,51Faculty of Medicine, Universitas Airlangga, Surabaya, Indonesia; 2Institute of Tropical Disease, Universitas Airlangga, Surabaya, Indonesia; 3Universitas Airlangga Hospital, Surabaya, Indonesia; 4Department of Medical Microbiology, Faculty of Medicine, Universitas Airlangga, Surabaya, Indonesia; 5Department of Medical Biochemistry, Faculty of Medicine, Universitas Airlangga, Surabaya, IndonesiaCorrespondence: SoetjiptoDepartment of Medical Biochemistry, Faculty of Medicine, Universitas Airlangga, Mayjen Prof. Moestopo Street, No. 47, Surabaya 60131, IndonesiaTel +62 81331340518Email soetjipto1950@gmail.comBackground: Morbidity and mortality from acquired immunodeficiency syndrome (AIDS) are often associated with the reactivation of a herpes virus infection. Human herpesvirus-6 (HHV-6) is usually common in childhood infections that remain latent and can act as opportunists during immunosuppression to reactivate and cause disease. In human immunodeficiency virus (HIV)-infected patients, the impact of HHV-6 infection can be an up-regulator of HIV replication and accelerate progress towards AIDS. However, studies on HHV-6 infection have never been done in Surabaya, Indonesia.Purpose: To determine the presence of HHV-6 infection among HIV-infected individuals residing in Surabaya, Indonesia.Patients and Methods: Plasma and peripheral blood mononuclear cells (PBMCs) were collected from 85 HIV-infected individuals in Universitas Airlangga Hospital, Surabaya, as well as 85 healthy controls. DNA extracted from PBMCs was subjected to PCR to determine HHV-6 infection, while plasma of HIV-infected individuals was used for viral RNA quantification using real-time PCR.Results: HHV-6 infection was detected in 17.6% (15/85) of HIV-infected individuals, and in 3.53% (3/85) of healthy controls. Thus, HHV-6 infection was more likely to be found in HIV-infected individuals than in healthy controls (odds ratio 5.85; 95% confidence interval, 1.6– 21). The HHV-6B was the most common subtype identified in both HIV-infected individuals (12/15) and healthy controls (3/3). The HHV-6A and co-infection between HHV-6A and HHV-6B were only found in HIV-infected individuals (2/15 and 1/15, respectively). Viral RNA load of HIV-infected individuals was not correlated to HHV-6 infection.Conclusion: Our results indicate the emergence of HHV-6 infection among HIV-infected individuals residing in Surabaya, Indonesia, and the risk of HHV-6 infection was higher in HIV-infected individuals than in healthy controls.Keywords: HHV-6, HIV-infected individuals, healthy controls, Surabaya, Indonesia